HEREDITARY HEMOCHROMATOSIS: A RARE DISEASE OR A DIFFICULT DIAGNOSIS FOR A GENERAL PRACTITIONER? - Морозова, Александра Валерьевна; Морозова, Ольга Александровна; Бичан, Николай Андреевич (Medicine in Kuzbass, 2025)
Hemochromatosis is a hereditary disease belonging to the group of storage diseases characterized by impaired iron metabolism with its pathological accumulation in vital organs, including the liver. Homozygosity for C282Y in the HFE gene occurs in 90% of the patients with hemochromatosis. The disease must be differentiated from iron overload syndrome, since iron deposition in the liver contributes to the progression of an already existing chronic diffuse liver disease. Treatment options at the stage of established hereditary hemochromatosis, when ferritin exceeds 1000 ng/mL, are limited because hemosiderin is degraded ferritin and is extremely difficult to remove from tissues. Diagnosis of hemochromatosis at the pre-clinical stage, including screening of first-degree relatives and patients with the clinical phenotype of the disease, is necessary.This article discusses current understanding of the etiopathogenesis, clinical manifestations, laboratory and instrumental diagnostics, and basic treatment methods for hemochromatosis.
Keywords: hemochromatosis; iron overload syndrome; ferritin; transferrin; phlebotomy; chelators